Peran Financial Inclusion Koperasi Syariah dan Orientasi Kewirausahaan Sebagai Upaya Permbadayaan UMKM Syariah Di Kota Malang - Mulyaningtyas, Mulyaningtyas (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2019)
The government realizes that the development of micro and small enterprises is still hampered by financing that is more expensive than conventional financing. The potential of micro, small and medium enterprises in Indonesia is inseparable from banking support in lending to micro, small and medium enterprises. Access to Islamic banking is arguably still limited compared to conventional banking. This makes micro, small and medium enterprises players sometimes choose financing from conventional banks compared to Islamic financial institutions, this can be realized through continuous synergy between Islamic banks and Islamic cooperatives. Islamic cooperatives in various regions are financial inclusion locomotives to deepen sharia-based micro, small and medium enterprises in Malang. Sharia-based micro, small and medium enterprises are micro, small and medium enterprises that only want to be served by Islamic financial institutions. So that the need to empower sharia micro, small and medium enterprises is currently very important, through entrepreneurial orientation and financial inclusion it is expected that it will increase the empowerment of Sharia micro, small and medium enterprises based on Islamic boarding schools in the city of Malang. The research objective is to improve the role of Islamic Financial Inclusion and Entrepreneurship Orientation to empower Sharia micro, small and medium enterprises in Malang City. This study uses the path analysis model. And the type of data used are primary and secondary data taken from respondents, namely Sharia micro, small and medium enterprises and Sharia Cooperatives. Based on the results of the study it was explained that Financial Inclusion of Islamic Cooperatives did not influence the empowerment of micro, small and medium enterprises. While the entrepreneurial orientation affects the empowerment of Islamic micro, small and medium enterprises in Malang. If financial inclusion is carried out well, which is supported by high entrepreneurial orientation, this will increase the empowerment of micro, small and medium enterprises.